Limb-Body Wall Complex: A rare case report and systematic review - Sutandi, Chatrine; Sanjaya , I Nyoman Hariyasa (Universitas Airlangga, 2026)
HIGHLIGHTS Evolution from suspected gastroschisis (17+1 weeks) to confirmed LBWC at 20 weeks with classic features (thoracoabdominal wall defect, intestinal malrotation, limb anomalies), aligned with a systematic review of 23 studies (155 cases) showing mainly second-trimester ultrasound diagnosis and uniformly poor prognosis. Early diagnostic pathways (2D/3D ultrasound ± Doppler; adjunct MRI/AFP/genetics) sharpen differentiation from gastroschisis/omphalocele and strengthen evidence for prenatal counseling, management (including termination and delivery planning), and postmortem confirmation. ABSTRACT Objective: To report a rare case of Limb-Body Wall Complex (LBWC) and to synthesize current evidence regarding its diagnostic features, clinical presentation, and outcomes through a structured literature review. Case Report: This study integrates a single case report with a structured review of published cases. A 29-year-old gravida 2 para 0 woman at 20 weeks of gestation presented with absent fetal movement and was diagnosed with intrauterine fetal death accompanied by multiple congenital anomalies. Initial antenatal ultrasound at 17 weeks and 1 day suggested gastroschisis; however, subsequent evaluation confirmed LBWC, characterized by thoracoabdominal wall defect, intestinal malrotation, and limb anomalies. Pregnancy termination was performed using misoprostol, and the fetus was delivered vaginally as a stillbirth. Diagnosis was confirmed macroscopically post-delivery. The literature review, conducted in accordance with PRISMA 2020 guidelines using PEOS criteria, identified 23 eligible studies comprising 155 cases. Most diagnoses were established in the first and second trimesters using ultrasound, with adjunctive imaging or genetic testing in selected cases. Across studies, LBWC consistently demonstrated a uniformly poor prognosis, with outcomes including intrauterine fetal demise, termination of pregnancy, or early neonatal death. Common findings included limb agenesis, scoliosis, short or absent umbilical cord, and organ evisceration. Most included studies were of moderate to high methodological quality. Conclusion: LBWC is a rare and lethal congenital anomaly. Early and accurate antenatal diagnosis, particularly through repeated ultrasound evaluation, is essential to guide clinical decision-making, parental counseling, and pregnancy management